Handbook of data compression - Salomon, D. (David); Motta, Giovanni; Bryant, David (Springer, 2010)
Data compression is vital to modern computing, and this comprehensive reference covers the many different types and methods of compression. It includes a detailed taxonomy, analysis of the most common methods, and detailed descriptions of how to use them.